METTL3 regulates alternative splicing of MyD88 upon the lipopolysaccharide‐induced inflammatory response in human dental pulp cells. Issue 5 (4th March 2018) - Feng, Zhihui; Li, Qimeng; Meng, Runsha; Yi, Baicheng; Xu, Qiong
Abstract: Dental pulp inflammation is a widespread public health problem caused by oral bacterial infections and can progress to pulp necrosis and periapical diseases. N6‐methyladenosine (m6A) is a prevalent epitranscriptomic modification in mRNA. Previous studies have demonstrated that m6A methylation plays important roles in cell differentiation, embryonic development and stress responses. However, whether m6A modification affects dental pulp inflammation remains unknown. To address this issue, we investigated the expression of m6A and N6‐adenosine methyltransferase (METTL3, METTL14) as well as demethylases (FTO, ALKBH5) and found that the levels of m6A and METTL3 were up‐regulated in human dental pulp cells (HDPCs) stimulated by lipopolysaccharide (LPS). Furthermore, we knocked down METTL3 and demonstrated that METTL3 depletion decreased the expression of inflammatory cytokines and the phosphorylation of IKKα/β, p65 and IκBα in the NF‐κB signalling pathway as well as p38, ERK and JNK in the MAPK signalling pathway in LPS‐induced HDPCs. The RNA sequencing analysis revealed that the vast number of genes affected by METTL3 depletion was associated with the inflammatory response. Previous research has shown that METTL3‐dependent N6‐adenosine methylation plays an important role in mRNA splicing. In this study, we found that METTL3 knockdown facilitated the expression of MyD88S, a splice variant of MyD88 that inhibits inflammatory cytokine production, suggesting that METTL3 might inhibit the LPS‐induced inflammatory response of HDPCs by regulating alternative splicing of MyD88. These data shed light on new findings in epitranscriptomic regulation of the inflammatory response and open new avenues for research into the molecular mechanisms of dental pulp inflammation.